2017
DOI: 10.3390/nu9091022
|View full text |Cite
|
Sign up to set email alerts
|

Flavonolignans Inhibit IL1-β-Induced Cross-Talk between Blood Platelets and Leukocytes

Abstract: Interleukin-1 beta (IL-1β)—the most potent pro-inflammatory is responsible for a broad spectrum of immune and inflammatory responses, it induces T-cell and B-cell activation and consequently the synthesis of other pro-inflammatory cytokines (such as IFN-γ and TNF). IL-1β induces the formation of blood platelet-leukocyte aggregates (PLAs), which suggests that IL-1β significantly affects the cross-talk between blood platelets and the immune response system, leading to coronary thrombosis. The aim of our study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…There are many studies presenting flavonolignans as having strong anti-inflammatory properties [ 52 , 53 , 54 ], resulting in significantly reduced production of pro-inflammatory cytokines. In our previous study, we also documented the anti-inflammatory properties of flavonolignans on IL-1β-induced human blood samples [ 29 ]. For this reason, we decided to verify the toxic effect of flavonolignans on blood platelets’ peripheral blood mononuclear cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies presenting flavonolignans as having strong anti-inflammatory properties [ 52 , 53 , 54 ], resulting in significantly reduced production of pro-inflammatory cytokines. In our previous study, we also documented the anti-inflammatory properties of flavonolignans on IL-1β-induced human blood samples [ 29 ]. For this reason, we decided to verify the toxic effect of flavonolignans on blood platelets’ peripheral blood mononuclear cell.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that silybin and silychristin inhibit the IL-1β-induced formation of blood platelet-leukocyte aggregates in whole blood samples in a dose-dependent manner, as well as leucocyte production of the pro-inflammatory cytokines-IL-2, TNF, INF-α, and INF-γ. Additionally, these two flavonolignans abolished the IL-1β-induced expression of mRNA for IFN-γ and TNF in leucocytes [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silybin is also studied as a potential anticancer and chemo-preventive agent [ 13 ]. Research performed last year demonstrates that silybin is able to inhibit serine proteases involved in the blood coagulation process [ 14 , 15 ], as well as reduce blood platelets’ response to physiological agonists [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the reduction of platelet response to collagen by flavonolignans was significantly lower than the effect on ADP-induced blood platelet activation. Additionally, we observed that these compounds are able to inhibit cross-talk between blood platelets and the immune response system [ 18 ].…”
Section: Discussionmentioning
confidence: 99%